How (not) to define "assisted dying" - Jones, David Albert (Journal of medical ethics, 2025)
In the last 20 years "assisted dying" (and/or its variants "assisted death", "assistance in dying", "aid in dying") has become increasingly prevalent as a term to denote the intentional ending of the life of a patient by or with the assistance of a doctor. However, there is no agreed definition. This paper focuses on the debate over the definition of this term in the UK. It notes that, broadly speaking, there are two ways in which "assisted dying" has been defined. There are generic definitions, which cover a variety of practices, including self-administration of a lethal drug (assisted suicide) and administration by a healthcare professional (euthanasia) with or without specific eligibility criteria. In contrast, there are stipulative definitions which limit the term to a particular practice, for example, assisted suicide (not euthanasia) of adults (not minors) who are terminally ill (not those with chronic conditions). Examples of the former kind of definition are provided by the British Medical Association in its 2020 members’ survey and the POSTbrief on Assisted dying. Examples of the latter are provided by the British Medical Journal and the British Broadcasting Corporation. This paper argues that stipulative definitions are problematic in that they exclude practices that are widely referred to as "assisted dying". The attempt to restrict the definition leads to the term being used inconsistently. Stipulative definitions can be used consistently if it is acknowledged that they are secondary to the generic sense. This matters because clarity of terminology is a prerequisite of rational debate.